Educational attainment of Eastern European pupils in primary schools in England: Implications for policy and practice (UCL Press, 2019)
The aim of this article is to explore the attainment of Eastern European children in primary schools in England. The research draws on detailed National Pupil Database and school census data for 586,181 pupils who completed Key Stage 2 in England in 2016. Two methodological approaches were used to analyse the data. First, the performance of all pupils was analysed by ethnic and language background to illustrate patterns of attainment for each group. Second, attainment data were further analysed by social background factors to explore the main factors influencing performance in schools and the reasons for underachievement. The main findings from the study confirm that a number of Eastern European pupils have low attainment, and their performance in English schools has been masked by government statistics that fail to distinguish between 'White Other' ethnic groups. The empirical data suggest that speakers of Czech, Slovak, Hungarian, Polish, Romanian, Latvian, Lithuanian and Bulgarian are particularly underachieving, and that the difference between their educational performance and others is larger than for any other main groups. There is also a wide variation in performance between regions in England, with large attainment gaps between Eastern European and White British children. Some of the main reasons for underachievement identified from the study are the lack of fluency in English, economic deprivation, a disrupted or non-existent prior education and parental lack of understanding of the British education system. Overall, this research confirms that the underachievement of Eastern European children remains a cause for concern and is obviously an issue that policymakers and schools need to address. Implications for policy and practice are discussed in the final section.